1980
DOI: 10.3168/jds.s0022-0302(80)83155-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Twinning on Lactation and Days Open in Holsteins

Abstract: Effects of twinning on lactation and days open in Holsteins were studied from calving records compiled by member surveys of Eastern Artificial Insemination Cooperative. Records of cows with 305-day mature-equivalent records from the Northeast Dairy Records Processing Laboratory were grouped according to whether the twin calving was associated with dystocia. Records of each cow that had a twin calving were paired with records of a single-calving control herdmate. In the twin group of 175 cows associated with dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1
4

Year Published

1989
1989
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 9 publications
2
13
1
4
Order By: Relevance
“…The longest interval from parturition to the next conception in spring is probably because of the delay in the breeding of dairy cows in the summer months (because of the heat stress, lower conception rate and poorer condition of nutrition). Consistent with the results of this study, previous studies reported the longer interval from parturition to conception for twin calvings than single ones (Chapin and Van Vleck, 1980;Gregory et al, 1990b;Eddy et al, 1991). Echternkamp and Gregory (1999) observed that the interval from parturition to first oestrus was shorter for dams birthing and nursing a single (56.9 days) than for dams birthing twins and nursing one (68.5 days) or two (69.6 days) calves.…”
Section: Open Dayssupporting
confidence: 92%
“…The longest interval from parturition to the next conception in spring is probably because of the delay in the breeding of dairy cows in the summer months (because of the heat stress, lower conception rate and poorer condition of nutrition). Consistent with the results of this study, previous studies reported the longer interval from parturition to conception for twin calvings than single ones (Chapin and Van Vleck, 1980;Gregory et al, 1990b;Eddy et al, 1991). Echternkamp and Gregory (1999) observed that the interval from parturition to first oestrus was shorter for dams birthing and nursing a single (56.9 days) than for dams birthing twins and nursing one (68.5 days) or two (69.6 days) calves.…”
Section: Open Dayssupporting
confidence: 92%
“…The median calving-to-conception interval for cows that had live twins was 220 days and was 250 days if at least 1 twin was stillborn, compared with 175 days for cows that had singletons. Previous studies 5,14,15 also found that the mean calving-to-conception interval as well as inseminations per conception were increased for cows that had twins. Twin parturitions increase the risk of several diseases that are risk factors for impaired reproductive performance, such as retained fetal membranes, metritis, and abortion.…”
Section: Discussionmentioning
confidence: 78%
“…Several factors may be responsible for these results. For example, twinning, as a causal factor for stillbirth (Silva del Río et al, 2007) is higher in multiparous cows (Cady and Van Vleck, 1978;Silva del Río et al, 2007) which in turn leads to a reduction in milk production (Chapin and Van-Vleck, 1980). In addition, higher-producing cows had greater reduction in milk yield due to health disorders such as mastitis (Rajala-Schultz et al, 1999) and this may also be the case for cows producing stillborn calves.…”
Section: Resultsmentioning
confidence: 99%